GLOBAL TRADE IN THE POST-PANDEMIC ERA: CHALLENGES AND OPPORTUNITIES FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN INTERNATIONAL MARKETS - Omar Al-Khalil (Modern American Journals, 2025)
The COVID-19 pandemic significantly disrupted global trade, leading to a range of challenges for businesses worldwide. Among the hardest hit were Small and Medium Enterprises (SMEs), which faced disruptions in supply chains, declining demand, and limitations in market access. However, the post-pandemic era also offers opportunities for SMEs to adapt to new global trade dynamics, leverage digital technologies, and diversify markets. This paper examines the challenges and opportunities that SMEs encounter in global trade after the pandemic. It discusses the impact of changes in international supply chains, trade policies, digital transformation, and shifting consumer behaviors. Through case studies and recent data, the paper provides actionable insights for SMEs seeking to thrive in the evolving global trade landscape. The research also suggests strategies for overcoming barriers and seizing emerging opportunities in international markets.
Keywords: Global Trade, Small and Medium Enterprises, Post-Pandemic Economy, International Markets, Trade Challenges, Digital Transformation, SMEs in Global Markets, Supply Chain Disruptions, Trade Policy, Globalization